1998
DOI: 10.1093/ajcn/68.2.389
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin and vitamin B-6 intakes and status and biochemical response to riboflavin supplementation in free-living elderly people

Abstract: Free-living elderly people aged > or = 65 y were recruited to assess riboflavin and vitamin B-6 intakes and status and the effect of riboflavin supplementation on biochemical indicators of these 2 vitamins. The status of riboflavin (erythrocyte glutathione reductase activation coefficient; EGRAC) and vitamin B-6 (plasma pyridoxal-5'-phosphate; PLP) were determined in a total sample of 92 subjects, from whom dietary intake data were obtained by using the diet history method (n = 83). Although dietary intakes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 18 publications
8
48
1
Order By: Relevance
“…For riboflavin, less than 10% of men and women had intakes below the LRNI, whereas 38% were judged deficient on the status measurement (EGRAC). This paradox has been noted before in this same population 15 and in other surveys of older people 16,17 . It was also a finding in the recent survey of school children 18 , where the status results were attributed to the sensitive assay used.…”
Section: Discussionsupporting
confidence: 75%
“…For riboflavin, less than 10% of men and women had intakes below the LRNI, whereas 38% were judged deficient on the status measurement (EGRAC). This paradox has been noted before in this same population 15 and in other surveys of older people 16,17 . It was also a finding in the recent survey of school children 18 , where the status results were attributed to the sensitive assay used.…”
Section: Discussionsupporting
confidence: 75%
“…This paradox has also been noted in other recent studies of older people in the UK (Bailey et al 1997;Madigan et al 1998). Table 3 lists mean values for the biochemical status indices where there were significant differences between free-living participants and those in institutions, and examines the percentage differences between these two population groups, adjusted for age (since there was a highly significant difference in age profile between the two groups) and for sex.…”
Section: Biochemical Status Indicessupporting
confidence: 58%
“…The adequacy of sample size was established from power calculations using typical variances from other similar investigations (Madigan et al, 1998). All potential subjects were initially screened for riboflavin status.…”
Section: Methodsmentioning
confidence: 99%
“…A supplementation level of 1.6 mg=day riboflavin for 12 weeks was chosen based on data from a previous riboflavin intervention ( Madigan et al, 1998) carried out at this centre (but not concerned with tHcy), which demonstrated that this amount significantly improved riboflavin status in elderly people. We therefore chose the same regimen in order to observe what effect, if any, a change in riboflavin status would have on plasma tHcy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation